Laboratory and Field Screening of Maize Varieties Against Fall Armyworm, Spodoptera frugiperda (J. E. Smith, 1797) (Lepidoptera: Noctuidae), at Gorkha, Nepal - Adhikari, Chiran; Tiwari, Sundar; Thapa, Resham Bahadur; Neupane, Saraswati; Sharma, Sheela Devi (Journal of Agriculture and Forestry University, 2025)
There are several production constraints in maize cultivation in Nepal, and fall armyworm (Spodoptera frugiperda J. E. Smith, 1797) is considered one. Fall armyworm (FAW) is an invasive, polyphagous, and voracious agricultural pest in maize crops. The current study aimed to understand the host plant selection behavior of the fall armyworm on different popular maize varieties in lab and field conditions. The lab experiment (choice test) was conducted at the Department of Entomology, AFU, in June 2022. Cohorts of fifteen third-instar larvae were used for laboratory bioassay in a Completely Randomized Design (CRD) with ten replications. Ten different maize varieties (7 open-pollinated varieties and 3 hybrids) represent treatments at both conditions, which are popular and recommended in Nepal. The number of larvae settled on each maize variety was counted at 1 hour, 4 hours, 12 hours, and 24 hours after larvae were released. The results showed that the selection of maize genotype by fall armyworm larvae was initially random. However, at the end of the experiment, there was a significant difference in the settlement of FAW larvae among the varieties. The larvae settled on different maize genotypes of their preference. Rampur Hybrid- 12 was least preferred whereas Posilo Makai- 1, Rampur Composite, Arun- 4, and Manakamana- 7 were more preferred by FAW. The field experiment was conducted in 2022 in Gorkha, Nepal. The experiment was carried out in Randomized Complete Block Design (RCBD) with ten treatments, which were replicated three times. The data were collected at every 10-day interval after 20DAS (V4 stage). Based on the percent plant infestation with live larvae and the intensity of foliar damage, Rampur Hybrid- 12, Deuti, and Manakamana- 3 were comparatively less attracted toward FAW. In contrast to that, Manakamana- 7, Rampur Hybrid- 16, Rampur Composite, Arun-4, and Arun- 2 were found to be more prone to fall armyworm attacks. Not all varieties are equally susceptible to FAW damage. These findings have important implications for understanding the range of preference by FAW on different maize varieties.